Effect of oral and intravenous iron therapy on hemoglobin levels in hemodialysis patients according to serum ferritin level. Issue 1 (December 2016) - Daimon, Shoichiro; Mizushima, Ichiro
Abstract Background For iron therapy in hemodialysis patients, intravenous rather than oral administration is recommended. Methods For hemodialysis patients with serum ferritin levels less than 200 ng/ml (less than 100 ng/ml: 67 patients, between 100 and 199 ng/ml: 20 patients) with no iron therapy for more than 3 months, iron was administered intravenously (40 mg of ferric oxide saccharate for ten times consecutively, N  = 40) or orally (50 mg/day of sodium ferrous citrateN  = 31, or 1500 mg/day of ferric citrate hydrateN  = 16). We conducted the retrospective observational study to evaluate the changes in hemoglobin levels, the dose of erythropoietin-stimulating agents (ESAs), and the ratio of ESA dose/hemoglobin (Hb) levels for 28 weeks. Results During the first 8 weeks, hemoglobin levels increased and ESA/Hb ratio decreased uniformly with almost the same ESA dose. Subsequently, ESA/Hb ratio increased in patients with intravenous iron but decreased further in patients administered oral iron. ESA dose reduction at the end of the study in the patients receiving intravenous iron, sodium ferrous citrate, and ferric citrate hydrate were 12.2, 33.8, and 39.5 %, and ESA/Hb reduction ratios were 10.3, 34.5, and 37.4 %, respectively. In patients with serum ferritin levels less than 100 ng/ml at baseline, ESA/Hb ratio decreased especially in those receiving oral rather than intravenous iron (p  < 0.05), while it did not change with either oral or intravenous iron in patients with serum ferritin levels between 100 and 199 ng/ml. Conclusions In hemodialysis patients with serum ferritin levels less than 100 ng/ml, oral iron therapy is an effective method to treat anemia.